69.8k views
4 votes
Please help as soon as possible

Find the inverse of the given function.

f(x) = -1/2√x + 3, x ≥ -3

1 Answer

4 votes

To solve this problem you must apply the proccedure shown below:

You must switch the variables, and then, you must solve for
y, as following:


x=-(1)/(2) √(y) +3\\ (x-3)^(2) = ((1)/(2)√(y))^(2) \\ y=4x^(2) -24x+36\\ f^(-1) (x)=4x^(2) -24x+36

Therefore, as you can see, the answer is:
f^(-1) (x)= 4x^(2) -24x+36

User Hesolar
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.